KROATISCHE UND DEUTSCHE ANTISPRICHWÖRTER IN DER SPRACHE DER JUGENDLICHEN - Aleksa Varga, Melita; Keglević, Ana (Proverbium - Yearbook, 2018)
The present paper discusses the results of a survey conducted among adolescents aged 11-20 in Croatia, Germany, and Austria. The survey is the extension of research conducted in Croatia in 2014 with 897 respondents aged 14-87, which showed that the adolescents aged 11-20 in 79.30% of cases filled the first part of proverbs with the wrong phrase, indicating that they might be more familiar with the particular anti-proverb than with the canonical form of a particular proverb (Aleksa Varga, Matovac 2016). The present research was conducted on a sample of 202 Croatian native speaker, and 144 German native speaker adolescents, by filling out a paper questionnaire and supplying the first part of the most frequently occurring proverbs in Croatian and German written corpora. All the “wrong” answers, that is the items that do not correspond to the zero variant have been collected in a special sub-corpus which has been analyzed in the course of the present paper, with the special aim of describing and analyzing the anti-proverbs adolescents have provided.